2009
DOI: 10.1051/0004-6361/200811293
|View full text |Cite
|
Sign up to set email alerts
|

Orbital modulation of X-ray emission lines in Cygnus X-3

Abstract: Aims. We address the problem where the X-ray emission lines are formed and investigate orbital dynamics using Chandra HETG observations, photoionizing calculations and numerical wind-particle simulations. The aims were to set constraints on the masses of the components of this close binary system consisting of a Wolf-Rayet (WR) star and a compact component and to investigate the nature of the latter (neutron star or black hole). The goal was also to investigate P Cygni signatures in line profiles.Methods. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
77
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 21 publications
11
77
0
Order By: Relevance
“…v wind in the line-forming region is substantially lower than the terminal wind velocity. Vilhu et al (2009) used Chandra HETG spectra to map the ionization and velocity fields of the wind in Cyg X-3, largely confirming the picture developed by van Kerkwijk et al (1996) and Hanson et al (2000) and showing that the wind is highly ionized out to many times the binary separation. The X-ray FeXXVI line RV curve appears to trace the compact object's motion, with the required phase relationship to the IR emission and absorption features, resulting in a mass function consistent with that obtained by Hanson et al (2000).…”
Section: Wind Ionization and Shadowingsupporting
confidence: 64%
See 1 more Smart Citation
“…v wind in the line-forming region is substantially lower than the terminal wind velocity. Vilhu et al (2009) used Chandra HETG spectra to map the ionization and velocity fields of the wind in Cyg X-3, largely confirming the picture developed by van Kerkwijk et al (1996) and Hanson et al (2000) and showing that the wind is highly ionized out to many times the binary separation. The X-ray FeXXVI line RV curve appears to trace the compact object's motion, with the required phase relationship to the IR emission and absorption features, resulting in a mass function consistent with that obtained by Hanson et al (2000).…”
Section: Wind Ionization and Shadowingsupporting
confidence: 64%
“…At the more moderate ionization fraction expected deep in the core of the wind (and especially in the shadow of the WR star), single-electron ions of e.g. O, C, Si, and Fe will be present (as seen by Vilhu et al (2009) in Cyg X-3) and contribute significant soft X-ray absorption.…”
Section: Spectral Analysis Of Ic10 X-1mentioning
confidence: 99%
“…Zdziarski et al (2013) have presented arguments based on the radial velocity variation of the compact object from X-ray spectral lines and the mass loss rate to conclude that the mass of the compact object is 2.4 +2.1 −1.1 M , which could either be a neutron star or a black hole. The broadband spectral properties, however, suggest a low mass black hole (Vilhu et al 2009;. The orbital modulation of the X-ray flux has been explained by a low temperature cloud of plasma surrounding the compact object asymmetrically, which Compton scatters the radiation (Zdziarski et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…To estimate cooling times we use the photoionisation model of Vilhu et al (2009), where the compact star luminosity is L x = 2.46 × 10 38 erg/s. The clump densities probably vary, as do their sizes, but as an example we use a density of 10 13 cm −3 .…”
Section: Cooling Times Of Shocked Clumpsmentioning
confidence: 99%
“…The data were limited to moderately high states (daily means ≥15 counts/s), to be more consistent with the Cygnus X-3 spectral state during the Chandra/HETG observations used. The emission line light curves (Si XIV Lyα 6.185 Å, FeXXVI Lyα 1.780 Å (H-type) and FeXXV 1.859 Å (He-type)) were taken from Vilhu et al (2009) and observed during a high state by Chandra/HETG (PI McCollough). The number of phase bins used was 30 and 10 for the continuum and lines, respectively.…”
Section: Modeling Of the X-ray Continuum And Emission Line Light Curvesmentioning
confidence: 99%